2018
DOI: 10.1126/science.aap7714
|View full text |Cite
|
Sign up to set email alerts
|

Ancient convergent losses ofParaoxonase 1yield potential risks for modern marine mammals

Abstract: Mammals diversified by colonizing drastically different environments, with each transition yielding numerous molecular changes, including losses of protein function. Though not initially deleterious, these losses could subsequently carry deleterious pleiotropic consequences. We have used phylogenetic methods to identify convergent functional losses across independent marine mammal lineages. In one extreme case, () accrued lesions in all marine lineages, while remaining intact in all terrestrial mammals. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 96 publications
3
83
0
1
Order By: Relevance
“…Unfortunately, such approaches still have limited utility in multicellular eukaryotes and likely don't reveal the full range of constraints operating in nature. An alternative and analogous approach is to examine evolutionary patterns in large, naturally occurring assemblages of species exhibiting parallel adaptations in response to a common selective pressure (Liu et al 2010;Meyer et al 2018;Zhen et al 2012;Dobler et al 2012;Christin et al 2007). Evolutionary studies of parallelisms are a powerful complementary approach to deducing the factors constraining the adaptation (Stern 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, such approaches still have limited utility in multicellular eukaryotes and likely don't reveal the full range of constraints operating in nature. An alternative and analogous approach is to examine evolutionary patterns in large, naturally occurring assemblages of species exhibiting parallel adaptations in response to a common selective pressure (Liu et al 2010;Meyer et al 2018;Zhen et al 2012;Dobler et al 2012;Christin et al 2007). Evolutionary studies of parallelisms are a powerful complementary approach to deducing the factors constraining the adaptation (Stern 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the contribution of mutations in such genes or regulatory elements to the evolution of a trait requires an experimentallytractable system, such as the mouse, where specific mutations can be introduced and their effects quantified. Gene knockout studies in mice contributed to our understanding of the functional role of many genes naturally lost in a variety of mammalian species (39)(40)(41)(42)(43)(44)(45)(46). However, the effect of other, much more frequent genomic changes, such as amino-acid changing mutations in protein-coding sequences and sequence changes in regulatory elements has rarely been explored.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we devised a novel approach to automate the survey of genomes for instances of coding gene sequence erosion. Knowledge of gene losses has far-reaching applications in studying the morphological and physiological adaptations of different species [10], in discovering alternative molecular pathways for critical genes [2], in medical genetics [13], and even in animal conservation programs [12]. We designed our approach for low false positive rates in order to be practically useful for the experimentalists tackling these research efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a few intriguing examples of gene losses that are 2 associated with phenotypic traits. For example, the enzyme gene GULO is inactivated in independent mammalian lineages that consequently lost the ability to synthesize Vitamin C, and must instead have a constant supply of it in their diet [3,4]; multiple visual system genes are no longer functional in subterranean mammals which live primarily in darkness [5,6]; taste receptor and other genes are lost in fully aquatic cetaceans [7][8][9]; renal transporter genes URAT1, GLUT9 and OAT1 are dead in fruit-eating bats, which could have facilitated their frugivorous diet [10]; the immune genes MX1 and MX2 are eroded in toothed whales, possibly making them more susceptible to certain viral pathogens [11]; and the loss of PON1 in several marine mammals may confer increased vulnerability to agricultural pesticide pollution [12]. Systematic annotation of gene losses across species may therefore not only reveal fascinating evolutionary events and genotype-phenotype relationships, but could also point us to "natural knockout" models for human pathologies that reveal compensating molecular pathways in species missing otherwise-indispensable genes [2,3,13].…”
Section: Introductionmentioning
confidence: 99%